2011
DOI: 10.1016/j.jmii.2011.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of uncommon emm types of Streptococcus pyogenes among adult patients in southern Taiwan

Abstract: These results suggest new emm types (emm11, emm81, and emm102) of S pyogenes were introduced into the adult population in southern Taiwan after 2004. The rarely reported emm types, including emm13, emm81, and emm106, caused invasive diseases more often in adult patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 27 publications
0
7
1
Order By: Relevance
“…Other than one study which reported that emm106 was one of the prevalent emm types in invasive GAS in New Caledonia (34), this emm type has not been reported in other countries. However, two studies in Taiwan found emm106 to be highly associated with invasive skin and soft tissue infections (28,30). Although we do not have information on the disease manifestations, we did find a strong association of emm106 with abscess/pus isolates.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Other than one study which reported that emm106 was one of the prevalent emm types in invasive GAS in New Caledonia (34), this emm type has not been reported in other countries. However, two studies in Taiwan found emm106 to be highly associated with invasive skin and soft tissue infections (28,30). Although we do not have information on the disease manifestations, we did find a strong association of emm106 with abscess/pus isolates.…”
Section: Discussioncontrasting
confidence: 70%
“…Three studies on invasive GAS, one from France, one from 11 European countries, and the other from the United States, also found emm1 to be the leading emm type among invasive GAS isolates (25)(26)(27). Previous studies from Taiwan have also found emm1, emm4, emm12, and emm11 to be among the prevalent emm types, but their proportions varied in different disease entities and populations (28)(29)(30). However, emm28, a leading emm type in Western countries associated with ERY-resistant GAS (5,25,26,31), was detected in only one of the ERY r isolates in the present study.…”
Section: Discussionmentioning
confidence: 93%
“…This type is highly prevalent in some parts of the world. 1 However, emm-type 89 was absent from a sample collected in India 8 and in a survey during 1997e2008 in Taiwan, 9 illustrating that the predominant emm types vary with geographical location. In mainland China, the most prevalent emm genotype identified from clinical specimen in recent years were emm 1.0, emm 12.0, emm 4.0, and emm 22.0.…”
Section: Discussionmentioning
confidence: 99%
“…Six hundred seventy-seven GAS isolates collected from 1994 to 2008 at National Cheng Kung University Hospital, Tainan, Taiwan, were included in this study. Among these isolates, 334 GAS isolates were collected consecutively from patients older than 20 years between 1997 and 2008 and were described in the previous study (29). An additional 276 isolates were collected from patients younger than 20 years from 1997 to 2008, and 67 isolates were collected from patients of all ages from 1994 to 1996 in this study.…”
Section: Methodsmentioning
confidence: 99%